Levofloxacin 복용 후 발생한 양측 아킬레스건 파열: 증례 보고 - 박철현; Chul Hyun Park (대한족부족관절학회지, 2025)
Levofloxacin is a broad-spectrum antibiotic, commonly used for respiratory and urinary tract infections. However, fluoroquinolone class antibiotics can cause Achilles tendon injury, and the risk is increased, especially in patients with chronic kidney disease. We report a case of a 63-year-old man with chronic kidney disease who developed bilateral Achilles tendon rupture 2 days after taking levofloxacin, and review the associated risk factors and pathophysiology.